Evaluation of F2 Mapping Population for Stem Rot Tolerance in Tossa Jute (Corchorus olitorius) - Meena, Jitendra Kumar; Bhandari, Hem Raj; Mangal, Vikas; Ray, Soham; Mandal, Kunal; Thribhuvan, R.; Chourasia, Kumar Nishant; Kar, Chandan Saurav; Bhowmick, Rakesh (International Journal of Bio-resource and Stress Management, 2024)
Present investigation was undertaken at ICAR-CRIJAF, Barrackpore, West Bengal, India during summer season (Apr–July) of 2020 to identify the jute breeding lines resistant to stem rot which is one of the major problems in jute production. The identified resistant and susceptible jute accessions (RS-6 and OIJ-272, respectively) were crossed to develop a mapping population for the disease. The resultant F2 population comprising 125 plants was screened for resistance to stem rot disease caused by Macrophomina phaseolina following artificial inoculation. The progress of infection was measured as the length of the infected stem portion (i.e., lesion length in cm) after 7, 14 and 21 days of inoculation (time replication). After stem inoculation investigation indicated that in the F2 population of the cross OIJ-272×RS-6, only 14 plants (PL-100, PL-40, PL-99, PL-33, PL-89, PL-119, PL-1, PL-43, PL-118, PL-121, PL-6, PL-11, PL-55 and PL-86) were found moderately resistant (lesion length 2.0–3.0 cm). In contrast, 10 plants (PL-4, PL-31, PL-19, PL-27, PL-3, PL-50, PL-18, PL-26, PL-47, PL-51) were found highly susceptible (lesion length >5.0 cm). The remaining 101 plants exhibited moderate susceptible symptoms. While the parent OIJ-272 exhibited high susceptibility to stem rot with an average lesion length of 5.53 cm, the parent RS-6 exhibited moderate resistant reaction with an average lesion length of 2.30 cm. Because of good resistance under artificial stem inoculation of this fungi, these 14 F2 plants of the cross can be further exploited for a resistance breeding programme against this deadly disease.